Evaluasi Usability Fitur Webshare Pada Aplikasi Share It Menggunakan Metode Thinking-Aloud - Lusi Rahmi (Universitas Multimedia Nusantara, 2019)
Share it is an application made by Lenovo which is a service for sharing various types of files, for example images, videos, applications or others.share it, which is currently widely used, has many functions that can help someone when sending and receiving files. One of them is sending files via the Webshare feature in the Share It application. Usability testing is a series of processes or activities that involve Respondents to find out how well a product (system) can be used easily by Respondents. This study discusses how easily Respondents send files via the Webshare feature in the Share It application. The method used here is Thinking-Aloud. The results obtained in this study are respondents who find it difficult when searching for Webshare features in the Share It application. We also provide advice on how to fix this problem with some references that we encountered on the internet.